The Value Equation: Three complementary propositions for reconciling fidelity and adaptation in evidence-based practice implementation - Ulrica von Thiele Schwarz; Gregory A. Aarons; Henna Hasson (BMC, 2019)
Abstract Background There has long been debate about the balance between fidelity to evidence-based interventions (EBIs) and the need for adaptation for specific contexts or particular patients. The debate is relevant to virtually all clinical areas. This paper synthesises arguments from both fidelity and adaptation perspectives to provide a comprehensive understanding of the challenges involved, and proposes a theoretical and practical approach for how fidelity and adaptation can optimally be managed. Discussion There are convincing arguments in support of both fidelity and adaptations, representing the perspectives of intervention developers and internal validity on the one hand and users and external validity on the other. Instead of characterizing fidelity and adaptation as mutually exclusive, we propose that they may better be conceptualized as complimentary, representing two synergistic perspectives that can increase the relevance of research, and provide a practical way to approach the goal of optimizing patient outcomes. The theoretical approach proposed, the "Value Equation," provides a method for reconciling the fidelity and adaptation debate by putting it in relation to the value (V) that is produced. The equation involves three terms: intervention (IN), context (C), and implementation strategies (IS). Fidelity and adaptation determine how these terms are balanced and, in turn, the end product - the value it produces for patients, providers, organizations, and systems. The Value Equation summarizes three central propositions: 1) The end product of implementation efforts should emphasize overall value rather than only the intervention effects, 2) implementation strategies can be construed as a method to create fit between EBIs and context, and 3) transparency is vital; not only for the intervention but for all of the four terms of the equation. Summary There are merits to arguments for both fidelity and adaptation. We propose a theoretical approach, a Value Equation, to reconciling the fidelity and adaptation debate. Although there are complexities in the equation and the propositions, we suggest that the Value Equation be used in developing and testing hypotheses that can help implementation science move toward a more granular understanding of the roles of fidelity and adaptation in the implementation process, and ultimately sustainability of practices that provide value to stakeholders.